GENOTYPE X ENVIRONMENT INTERACTIONS AND STABILITY ANALYSIS IN ELITE LINES OF GARLIC (ALLIUM SATIVUM L.) - SANGEETA SHREE; A. B. SINGH; NITISH DE (The Bioscan, 2014)
Genotype response to changeable environmental factors as ex-pressed through genotype x environment interaction offers important information to growers as end users .Twenty five genotypes of garlic (Allium sativum L) were evaluated for their stability, with respect to yield and its contributing traits, in three different nutritional environments created with respect to different fertility levels for two consecutive years. The pooled analysis of variance indicated that genotype x environment interactions were highly significant for the characters viz., number of leaves per plant, length of leaf, yield per plant (weight of bulb), number of cloves per bulb, diameter of clove and average weight of clove and these characters were subjected to stability analysis. Linear as well as non-linear component of GxE interactions were found to be significant for these characters indicating that response of genotypes varied in different environments. In general, all the genotypes did not show any uniform stability and linear pattern for all the traits. Genotypes Bombay White Garlic (27.48,1.0934 and -0.0427), Dholi Garlic-1 (11.50, 1.3196 and -0.4346), Surajgarha Garlic Pink (23.87, 1.2118 and-0.5042) and Munger Garlic White (22.28,0.6110 and -0.1628) had high mean value over population mean, closer to one regression coefficient (bi ) and low and non-significant deviation from regression and was highly stable for yield per plant. These genotypes are likely to perform well in all the six environments.